“The Vision of St. Bernard” by Filippino Lippi and Its Legacy in the Florentine Painting of the Early 1500’s - Lopukhova, Marina A. (Actual Problems of Theory and History of Art, 2016)
This article discusses the receptions of the altarpiece “The Vision of St. Bernard” by Filippino Lippi (1485–88, Florence, Badia) in the art of Piero di Cosimo and some minor Florence painters at the turn of the 15th–16th centuries. It reviews the iconography of the Doctrina in Florentine art of the 14th–16th centuries and outlines formal, stylistic, and iconographic features of Filippino’s painting. It also considers specific examples of the borrowings from this composition in Florentine art, primarily in the predellas, by the minor masters who directly relate to Lippi, i.e. Raffaellino del Garbo and Master of Serumido, as well as in the unknown master’s drawing in the collection of the Uffizi Gallery which possibly originates from the artist’s workshop.
Keywords: Italian painting; Renaissance art; Florentine school; iconography of Saint Bernard; Filippino Lippi; Piero di Cosimo; Raffaellino del Garbo